Particles containing an antibacterial metal component and having cavities inside a shell containing silicon, and substrate with a transparent coating containing said particles
Particles with a silicon-containing outer shell and hollow interior, combined with antibacterial metal components, address the challenge of creating a transparent film with high reflection prevention, antibacterial performance, and structural integrity, enhancing film properties.
Patent Information
- Application Number
- JP2021012264
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-28
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-01-28
AI Technical Summary
Existing technologies face challenges in creating a transparent film with high reflection prevention, antibacterial performance, and sufficient hardness and strength, often leading to increased costs and decreased productivity due to separate production of antibacterial and reflection prevention layers.
The development of particles with a silicon-containing outer shell and hollow interior, incorporating 0.5 to 40% antibacterial metal components by oxide standard, with a cavity ratio of 10 to 90%, which are used to create a transparent film with enhanced antibacterial, reflection prevention, and structural integrity.
The particles provide a transparent film with high adhesion, sufficient hardness, strength, and antibacterial performance, achieving improved transparency and reflection prevention while maintaining structural integrity.
Smart Images

Figure 0007625427000001 
Figure 0007625427000002 
Figure 0007625427000003
Abstract
Description
[Technical field]
[0001] The present invention relates to particles that contain an antibacterial metal component and have an outer shell containing silicon and an inner cavity, and also to a substrate with a transparent coating that contains the particles. [Background technology]
[0002] Conventionally, in order to prevent reflection on the surface of a substrate such as a sheet or lens made of glass or plastic, an anti-reflection film is formed on the surface. For example, a coating film made of a low refractive index material such as fluororesin or magnesium fluoride is formed on the surface of a substrate such as glass or plastic by a coating method, a vapor deposition method, a CVD method, or the like. However, these methods are expensive in terms of cost. Therefore, it is known to form an anti-reflection film by applying a coating liquid containing composite oxide colloidal particles made of silica and an inorganic oxide other than silica and having a refractive index of 1.36 to 1.44 to the surface of the substrate (see, for example, Patent Document 1).
[0003] Also, a method for producing particles having an outer shell and a cavity therein is known (see, for example, Patent Documents 2 and 3). These particles have a lower refractive index than solid particles, and a transparent coating formed using these particles has a low refractive index and excellent antireflection performance.
[0004] It is also known that particles of inorganic oxides such as alumina and silica, or composite oxides such as silica-alumina, can be made antibacterial by carrying metal components such as silver and copper (see, for example, Patent Documents 4 and 5). Furthermore, an antireflection film having an antireflection layer and a layer having an antibacterial function is known (see Patent Document 6). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-133105 [Patent Document 2] JP 2001-233611 A [Patent Document 3] JP 2013-226539 A [Patent Document 4] Japanese Patent Application Publication No. 7-196424 [Patent Document 5] JP 2010-273698 A [Patent Document 6] Japanese Patent Application Publication No. 11-052105 Summary of the Invention [Problem to be solved by the invention]
[0006] Particles with cavities inside have a lower refractive index than particles with a filled interior. Therefore, when these are used in a coating, the transparency and anti-reflection performance of the coating are improved. Incidentally, components that require transparency and anti-reflection performance include, for example, display devices with touch panels such as smartphones, ATMs, and ticket vending machines. The surfaces of these devices are often contaminated by fungi such as Escherichia coli and Staphylococcus aureus, and various viruses, and antibacterial properties are required from a hygienic standpoint.
[0007] It has been known that antibacterial agents are applied to the surface of a coating film to impart antibacterial properties. For example, if an organic antibacterial agent is used, the coating itself is relatively easy, but there is a risk that the coating film may be damaged by a solvent, and there is a problem with the durability of antibacterial performance in terms of adhesion to the coating film and scratch resistance. On the other hand, if an inorganic antibacterial agent is present in the coating film, the durability of antibacterial performance can be expected, but a coating film containing the agent must be prepared separately. However, if the antireflection layer and the antibacterial layer are prepared separately, the effect of the layer other than the outermost surface may be insufficient, or the productivity may decrease, resulting in an increase in production costs. On the other hand, if a low refractive index component and an antibacterial component are blended in one coating film, the antireflection performance and antibacterial performance may be insufficient, or the transparency and strength of the coating may be insufficient.
[0008] Therefore, there is a demand for particles that have high transparency and anti-reflection properties when used in a coating, as well as high antibacterial properties.
[0009] In addition, substrates with transparent coatings (anti-reflective coatings) using these particles are required to have high transparency and anti-reflective properties, sufficient hardness and strength, and high antibacterial properties. [Means for solving the problem]
[0010] In order to solve these problems, the following particles were found.
[0011] The particles have a shell containing silicon and a cavity inside, and contain 0.5 to 40 mass% of an antibacterial metal component on an oxide basis. The proportion of cavities in the particles (porosity) is 10 to 90%, and the number of particles with one cavity is 80% or more of all particles.
[0012] The particles have a low refractive index, sufficient hardness and strength, high dispersibility, and high antibacterial properties. A coating solution containing such particles can provide a transparent coating film with high transparency and antireflection properties, sufficient hardness (pencil hardness), strength (scratch resistance), and high antibacterial properties. Effect of the Invention
[0013] The particles of the present invention provide a coating solution capable of producing a coating film having high transparency and antireflection properties, excellent adhesion to a substrate, sufficient hardness and strength, and high antibacterial properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The particles according to the present invention (hereinafter, the particles according to the present invention may be simply referred to as "particles") contain 0.5 to 40% by mass of an antibacterial metal component based on the oxide. The particle has a shell containing silicon and a cavity inside the shell. The proportion of the cavities in the particle (porosity) is 10 to 90%, and the proportion of particles having one cavity inside the shell to the total number of particles is 80% or more.
[0015] When the content of the antibacterial metal component in the particles is in the range of 0.5 to 40 mass % on an oxide basis, when these particles are used for a coating, a coating having high antibacterial properties, high transparency and anti-reflection ability can be obtained.
[0016] Here, if the content of the antibacterial metal component is less than 0.5% by mass, sufficient antibacterial performance may not be obtained. Conversely, if the content exceeds 40% by mass, the antibacterial performance will not be further improved, and in some cases the antibacterial metal component may become unstable, and may be easily separated from the particles, discolored, etc. In addition, there is a risk of a decrease in transparency and antireflection performance. The content of this antibacterial metal component is preferably 1 to 30% by mass, more preferably 3 to 10% by mass.
[0017] The shell of the particle contains silicon. The silicon-containing material is preferably an oxide. Examples of the silicon-containing oxide include oxides containing at least one element selected from aluminum, zirconium, titanium, zinc, tin, and antimony and silicon, and silica. These oxides may be used alone, in the form of a mixture, or in the form of a composite oxide.
[0018] The inclusion of silicon in the shell reduces the refractive index of the particles and improves the compatibility between the particles and the matrix forming components. This allows the formation of a transparent coating with low reflectance, and the particles can be highly dispersed in the transparent coating, improving the strength of the coating. The silicon content contained in the particles is preferably 50% by mass or more when expressed as silica. The silicon content is more preferably 75% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass.
[0019] The porosity of the particles is 10 to 90%. If the porosity is less than 10%, when the particles are used in a coating, a coating having sufficient transparency and anti-reflection properties cannot be obtained. Conversely, if the porosity exceeds 90%, the particle structure is too "sparse" and the structure may not be maintained, or even if it is maintained, a coating having sufficient hardness and strength may not be obtained. The porosity is preferably 13 to 80%, more preferably 20 to 70%.
[0020] The number ratio of particles with one cavity to the total number of particles is 80% or more. If the number ratio is less than 80%, when these particles are used in a coated substrate, the transparency and anti-reflection performance may be insufficient. The number ratio is preferably 95% or more, more preferably 99% or more, and most preferably 100%.
[0021] In addition, the cavity inside the shell preferably has a shape that follows the outer shape of the particle. In other words, the more uniform the thickness of the shell, the better. Although it depends on the thickness of the shell, sufficient hardness and strength can be obtained even when stress is applied to the particle.
[0022] The antibacterial metal component preferably contains an element selected from silver, copper, zinc, lead, tin, bismuth, cadmium, chromium, mercury, nickel, and cobalt. These metal elements may be used alone or in combination. More preferred metal elements are silver, copper, and zinc, and even more preferred are silver and zinc.
[0023] The density (A1) of the particles measured by a He gas adsorption method is preferably 1.95 to 3.50 g / ml, and the density (B1) measured by a N2 gas adsorption method is preferably 0.50 to 2.60 g / ml.
[0024] The density by the gas adsorption method is obtained by drying the particle dispersion in an evaporator, heat-treating (drying) the resulting solution in air at 105°C, and measuring it with a dry automatic density meter (Micromeritics Corp., AccuPyc1340TC) using He gas or N2 gas. The density (A2) and density (B2) described below are obtained by similarly measuring the powder dried in the evaporator described above, heat-treating (firing) it in air at 400°C.
[0025] Although the details of why the density range differs depending on the gas type used for measurement are unclear, it is believed that the adsorption state due to differences in gas types is expressed as a numerical value in relation to the surface condition of the particles, such as the unevenness and pores on the particle surface.
[0026] If the density (A1) is less than 1.95 g / ml, the amount of the antibacterial metal component is small, and there is a risk that sufficient antibacterial performance cannot be obtained. On the other hand, if the concentration exceeds 3.50 g / ml, the supported antibacterial metal component becomes unstable and is likely to become detached from the particles, discolor, etc. Also, there is a risk of a decrease in transparency, anti-reflection ability, strength, and adhesion.
[0027] Moreover, it is difficult to obtain particles having a density (B1) of less than 0.50 g / ml because the shell structure cannot be maintained.
[0028] On the other hand, if the concentration exceeds 2.60 g / ml, the supported antibacterial metal component becomes unstable and is likely to separate from the particles, discolor, etc. Also, there is a risk of a decrease in transparency, anti-reflection ability, hardness, and adhesion.
[0029] The density (A1) is more preferably from 2.00 to 3.00 g / ml, and further preferably from 2.10 to 2.30 g / ml.
[0030] The density (B1) is more preferably 0.80 to 2.10 g / ml, and further preferably 0.90 to 1.50 g / ml.
[0031] The density (A2) of the particles heat-treated at 400° C., as measured by He gas adsorption, is preferably 2.17 g / ml or more.
[0032] Here, if the density (A2) is less than 2.17 g / ml, the amount of the antibacterial metal component is small, and there is a risk that sufficient antibacterial performance cannot be obtained.
[0033] The upper limit of density (A2) is not particularly set. However, depending on the type of antibacterial metal component, when it is used as a transparent coated substrate, the reflectance or haze may increase, or the transmittance, strength, and adhesion may decrease. For this reason, for example, the upper limit of density (A2) is 3.70 g / ml when the antibacterial metal component is silver, 3.50 g / ml when the antibacterial metal component is copper, and 3.20 g / ml when the antibacterial metal component is zinc.
[0034] The density (A2) is more preferably 2.20 g / ml or more, and further preferably 2.24 g / ml or more.
[0035] The ratio (A2 / B2) of the density (A2) to the density (B2) of the particles heat-treated at 400° C. as determined by N 2 gas adsorption method is preferably 1.10 or more.
[0036] If the ratio (A2 / B2) is less than 1.10, the refractive index of the particles will be high, and the anti-reflection performance of the coating may become insufficient.
[0037] The upper limit of the ratio (A2 / B2) is not particularly set, but is, for example, 4.50, since there is a risk that the structure of the outer shell may not be maintained.
[0038] The ratio (A2 / B2) is more preferably 1.30 or more, and further preferably 1.45 or more.
[0039] The average particle size of the particles is not particularly limited, but is preferably 20 to 180 nm when used as a substrate with a transparent film. When the average particle size is within this range, the particles can exist stably. In addition, the particles have good dispersibility in the coating solution and the coating, and a coating having high transparency, hardness and strength can be obtained. The average particle size is more preferably 30 to 120 nm, and even more preferably 40 to 110 nm.
[0040] The average thickness of the shell is preferably 5 to 30 nm. This allows the shell structure to be stably maintained, allowing the particles to exist stably. Also, a coating with high transparency, hardness, and strength is obtained. Here, if the shell is thin with an average thickness of less than 5 nm, the particle structure may not be maintained. Conversely, if it exceeds 30 nm, the refractive index of the shell may become too high, depending on the type and amount of the antibacterial metal component. The average thickness is more preferably 5 to 20 nm, and even more preferably 7 to 12 nm.
[0041] The alkali metal content of the particles is preferably less than 1.00 mass % on an oxide basis.
[0042] Here, if the content is 1.00% by mass or more, the particles may be cohered with each other, the dispersibility of the particles in the coating solution or the coating film may decrease, sufficient film hardness may not be obtained, or transparency may become insufficient. The alkali metal content is more preferably less than 0.10% by mass, even more preferably less than 0.01% by mass, and most preferably does not contain any alkali metal. When the particles contain an alkaline earth metal, the above-mentioned "alkali metal content" is to be read as "the total content of the alkali metal and the alkaline earth metal". The alkali metals are Li, Na, K, Rb, Cs, and Fr, and the alkaline earth metals are Be, Mg, Ca, Sr, Ba, and Ra.
[0043] The particles of the present invention can also be dispersed in an organic substance such as an organic solvent or an organic resin. In this case, it is preferable to use an organosilicon compound to surface-treat the particles. As the organosilicon compound, it is preferable to use an organosilicon compound (n is 1 to 3) represented by the following formula (1). Here, when an organosilicon compound in which n is 0 is used, it is preferable to use a partial hydrolyzate of the organosilicon compound. By this surface treatment, the particles contain an organic compound having a functional group derived from the organosilicon compound represented by the following formula (1). The functional group is at least one selected from an alkyl group, an epoxy group, a vinyl group, a (meth)acryloxy group, a mercapto group, an amino group, a phenyl group, and a phenylamino group.
[0044] R n -SiX 4-n ...Equation (1) (In the formula, R represents an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, and may be the same or different. Examples of the substituent include an epoxy group, a vinyl group, a (meth)acryloxy group, a mercapto group, an amino group, and a phenylamino group. X represents an alkoxy group having 1 to 4 carbon atoms, a hydroxy group, a halogen atom, or a hydrogen atom, and n represents an integer of 0 to 3.)
[0045] Specific examples of the organic silicon compound include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, isobutyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, 7-octenyltrimethoxysilane 3, 3,3-Trifluoropropyltrimethoxysilane, methyl-3,3,3-trifluoropropyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, 8-glycidoxyoctyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane silane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-acryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltri Examples of suitable silanes include methoxysilane, γ-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-isocyanatopropyltriethoxysilane, trimethylsilanol, n-propyltrimethylsilane, n-propyltriethylsilane, p-styryltrimethoxysilane, methyltrichlorosilane, methyldichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, vinyltrichlorosilane, trimethylbromosilane, and diethylsilane.
[0046] The surface treatment of the particles is carried out by preparing a dispersion of the particles in at least one of water and alcohol, adding a predetermined amount of the organosilicon compound represented by formula (1) and, if necessary, water to the dispersion to hydrolyze the organosilicon compound. In this hydrolysis, an acid or an alkali is used as a hydrolysis catalyst, if necessary. Furthermore, if necessary, impurities may be reduced by ion exchange, ultrafiltration, etc., at least either before or after the surface treatment.
[0047] The organic silicon compound has R in the particles. n -SiO (4-n) / 2 It is preferable that the content is 0.1 to 30 mass % (solid content). If the particles are surface-treated with an organosilicon compound, the compatibility with the matrix-forming components is improved.
[0048] Here, if the amount of the organosilicon compound is less than 0.1% by mass, the effect of adding the organosilicon compound is not sufficient. If the amount of the organosilicon compound is more than 30% by mass, not only will the dispersibility of the particles not be further improved, but there is also a risk that sufficient antibacterial performance will not be obtained. The amount of the organosilicon compound is more preferably 1 to 25% by mass, further preferably 1 to 20% by mass, and particularly preferably 1 to 15% by mass.
[0049] The shape of the particles is not particularly limited. For example, it may be spherical, ellipsoidal (rugby ball), cocoon-like, confetti-like, chain-like, dice-like, etc. Among them, spherical particles are preferred because they have high dispersibility and can be uniformly dispersed in the coating.
[0050] [Substrate with transparent film] The substrate with a transparent coating according to the present invention is a substrate with a transparent coating comprising the above-mentioned particles and a matrix formed on the substrate. The matrix is a solid component other than the particles, and includes resins derived from the coating liquid, and additives such as polymerization initiators and leveling agents. Specifically, the coating liquid is applied to the substrate by a known method, and then dried and irradiated with ultraviolet light to form a coating on the substrate. In the coating, the ratio of the solid components of the particles and matrix-forming components in the coating liquid is the same as the ratio of the particle components and matrix in the coating.
[0051] Between the transparent coating and the substrate, a conventionally known hard coat layer, anti-glare layer, high refractive index layer, conductive layer, etc. may be disposed depending on the application. A plurality of these layers may be combined. For example, in the case of further reducing the reflectance for display applications, a combination of a hard coat layer and a high refractive index layer, or a combination of a hard coat layer and an anti-glare layer may be exemplified.
[0052] The thickness of the transparent coating can be appropriately selected depending on the application. For example, for an anti-reflection coating, the thickness is preferably 80 to 350 nm.
[0053] Here, if the film thickness is less than 80 nm, the strength and scratch resistance of the film may be insufficient. Also, if the film is too thin, sufficient antireflection performance may not be obtained. Conversely, if the film thickness is more than 350 nm, the antireflection performance may be reduced. Also, if the shrinkage is very large, cracks may occur. This film thickness is more preferably 85 to 220 nm, and further preferably 90 to 110 nm.
[0054] The reflectance of the coated substrate is preferably 2.0% or less, and more preferably 1.5% or less.
[0055] The haze of the coated substrate is preferably 3.0% or less, and more preferably 0.3% or less.
[0056] The light transmittance of the coated substrate is preferably 85.0% or more.
[0057] Here, if the light transmittance is less than 85.0%, there is a risk that the clarity of the image will be insufficient in a display device, etc. This light transmittance is more preferably 90.0% or more.
[0058] The antibacterial activity test of the coating is carried out in accordance with JIS Z 2801. It is preferable that the antibacterial activity value is 2.0 or more. If it is 2.0 or more, it can be judged to have antibacterial activity. The antibacterial activity value is more preferably 4.0 or more.
[0059] The strength of the coating (scratch resistance) was measured using #0000 steel wool with a load of 1000g / cm 2 The film is evaluated by rubbing against a surface of the film at a temperature of 100° C. It is preferable that no streaky scratches are observed on the film surface after rubbing at least 100 times. More preferably, the scratch resistance is such that no scratches are observed after 500 times, and even more preferably, no scratches are observed after 1000 times.
[0060] The pencil hardness of the coating is preferably H or more. If it is less than H, the hardness is insufficient as an anti-reflection film. The pencil hardness is more preferably 2H or more, and further preferably 4H or more.
[0061] The substrate may be a known one. For example, a transparent resin substrate such as glass, polycarbonate, acrylic resin, polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyimide, polymethyl methacrylate resin (PMMA), or cycloolefin polymer (COP) is preferred. These substrates have excellent adhesion to the transparent coating formed by the above-mentioned coating liquid, and a substrate with a coating excellent in hardness, strength, etc. can be obtained. For this reason, it is suitable for use with thin substrates. There is no particular restriction on the thickness of the substrate, but it is preferably 10 to 100 μm, and more preferably 20 to 80 μm.
[0062] [Method of producing particles] The method for producing particles according to the present invention includes a first step of producing a first particle having a silica-containing shell and an internal cavity, and a second step of loading an antibacterial metal component onto the first particle.
[0063] Here, the first particles in the first step may be prepared by a conventional method (e.g., Patent Documents 2 and 3). The antibacterial metal component in the second step can be supported by adding it as a solution of a metal salt such as a hydrochloride, a nitrate, a sulfate, or an acetate, a metal complex ion, or a metal alkoxide solution. Among them, in the case of silver, silver nitrate is more preferable, and in the case of copper, zinc, or tin, hydrochloride, nitrate, sulfate, or acetate is more preferable.
[0064] The amount of the antibacterial metal component added is such that the final content of the antibacterial metal component in the particles is 0.5 to 40 mass% based on the oxide. When adding, multiple types of antibacterial metal components may be added separately or simultaneously. In addition, in order to increase the content, the antibacterial metal components may be added in multiple batches.
[0065] The conditions for adding the antibacterial metal component are not particularly limited as long as the final antibacterial metal component content is the desired one, but the concentration of the dispersion of the first particles is preferably 0.1 to 10 mass% as solid content. The pH when adding the antibacterial metal component is preferably 6 to 13, more preferably 8 to 10. If the pH is less than 6, the particles may become unstable and may aggregate. Conversely, if the pH exceeds 13, the particles themselves may dissolve, and the antibacterial metal component may not be sufficiently supported. The temperature when adding the antibacterial metal component is preferably less than the boiling point of the solvent. For example, if the solvent is water, the temperature is preferably less than 100°C, more preferably 30 to 95°C.
[0066] In order to reduce the content of alkali metals and alkaline earth metals in the particles, it is preferable to wash using an ion exchange resin or an ultrafiltration membrane after the second step. The total content of the alkali metals and alkaline earth metals is preferably less than 1.0 mass% on an oxide basis. In order to achieve this content, the first particles may be produced in advance using a raw material with a low content of alkali metals and alkaline earth metals, or the content of alkali metals and alkaline earth metals in the first particles may be reduced by performing ion exchange or the like in the first step. In addition, it is also possible to use a material containing an antibacterial metal with a low content of alkali metals and alkaline earth metals (for example, a metal alkoxide containing an antibacterial metal component) in the second step. Furthermore, these may be combined.
[0067] The finally obtained particles may be used as an aqueous dispersion, or may be substituted with an organic solvent, or may be further dried and used as a powder.
[0068] [Coating liquid for film formation] The particles of the present invention can be applied to a coating solution for forming a film. This coating solution contains the particles and a matrix forming component. In addition to these, the coating solution may contain additives such as an organic solvent, a polymerization initiator, a leveling agent, and a surfactant.
[0069] The concentration of particles in the coating liquid is preferably 5 to 95% by mass as solid content based on the total amount of solid content such as particles and matrix forming components contained. If the particle concentration is less than 5% by mass, the refractive index of the coating film may not be sufficiently reduced. Conversely, if it is higher than 95% by mass, cracks may occur in the coating film, adhesion to the substrate may be insufficient, and hardness, strength, transparency, haze, etc. may be deteriorated. The particle concentration is more preferably 10 to 85% by mass, and even more preferably 20 to 70% by mass.
[0070] The matrix-forming component is preferably an organic resin-based matrix-forming component, such as a matrix-forming component of an ultraviolet-curable resin, a thermosetting resin, or a thermoplastic resin.
[0071] Examples of ultraviolet-curable resins include (meth)acrylic acid resins, γ-glycyloxy resins, urethane resins, and vinyl resins.
[0072] Examples of the thermosetting resin include urethane resin, melamine resin, silicon resin, butyral resin, reactive silicone resin, phenol resin, epoxy resin, unsaturated polyester resin, and thermosetting acrylic resin.
[0073] Examples of the thermoplastic resin include polyester resin, polycarbonate resin, polyamide resin, polyphenylene oxide resin, thermoplastic acrylic resin, vinyl chloride resin, fluororesin, vinyl acetate resin, and silicone rubber.
[0074] These resins may be copolymers or modified products of two or more kinds, or may be used in combination. Furthermore, these resins may be emulsion resins, water-soluble resins, or hydrophilic resins.
[0075] The components forming these resins are preferably monomers or oligomers in view of particle dispersibility and ease of coating.
[0076] The concentration of the matrix-forming component in the coating liquid is preferably 5 to 95% by mass as solid content based on the total amount of solid content such as particles and matrix-forming components contained therein. If the concentration of the matrix-forming component is less than 5% by mass, it is difficult to form a film. Even if a film is obtained, cracks may occur in the film, adhesion to the substrate may be insufficient, and hardness, strength, transparency, haze, etc. may be deteriorated. Conversely, if it is higher than 95% by mass, the amount of particles is small, so that the refractive index may not be sufficiently reduced. The concentration of the matrix-forming component is more preferably 15 to 90% by mass, and even more preferably 30 to 80% by mass.
[0077] The organic solvent used can disperse particles uniformly and dissolve or disperse additives such as matrix forming components and polymerization initiators. Among them, hydrophilic solvents and polar solvents are preferred. Examples of hydrophilic solvents include alcohols, esters, glycols, and ethers. Examples of polar solvents include esters and ketones.
[0078] The alcohols include methanol, ethanol, propanol, 2-propanol, butanol, diacetone alcohol, furfuryl alcohol, and tetrahydrofurfuryl alcohol.
[0079] Examples of esters include methyl acetate, ethyl acetate, isopropyl acetate, propyl acetate, isobutyl acetate, butyl acetate, isopentyl acetate, pentyl acetate, 3-methoxybutyl acetate, 2-ethylbutyl acetate, cyclohexyl acetate, and ethylene glycol monoacetate.
[0080] The glycols include ethylene glycol and hexylene glycol.
[0081] Examples of ethers include diethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol isopropyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate.
[0082] Examples of ketones include acetone, methyl ethyl ketone, methyl isobutyl ketone, butyl methyl ketone, cyclohexanone, methylcyclohexanone, dipropyl ketone, methyl pentyl ketone, and diisobutyl ketone.
[0083] Other polar solvents include dimethyl carbonate and toluene.
[0084] These may be used alone or in combination of two or more.
[0085] Any additive that can be used in the past for forming an anti-reflective film can be used as the additive. For example, a polymerization initiator, a leveling agent, etc. can be used to promote polymerization of the matrix-forming components and improve film-forming properties.
[0086] Examples of the polymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)2,4,4-trimethyl-pentylphosphine oxide, 2-hydroxymethyl-2-methylphenyl-propane-1-ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, and the like.
[0087] Examples of the leveling agent include acrylic leveling agents, silicone leveling agents, acrylic silicone leveling agents, etc. Among these leveling agents, those having a fluorine group are preferably used.
[0088] Regarding the concentration of these additives in the coating liquid, those contained as solids when the coating is formed are counted as matrix forming components for convenience, and after coating, they are counted as the matrix.
[0089] The solid content concentration of the coating liquid (the ratio of the total solid content of the particles and the solid content of the matrix-forming components to the coating liquid) is preferably 0.1 to 100% by mass.
[0090] Here, if the solid content concentration of the coating solution is less than 0.1% by mass, the coating may be difficult to apply due to low concentration stability of the coating material, and it may be difficult to obtain a uniform coating film. In addition, the coating may have haze or poor appearance, which may reduce productivity, manufacturing reliability, etc. A coating solution having a solid content concentration of 100% by mass means that no organic solvent is present in the coating solution. The solid content concentration of the coating solution is more preferably 1 to 50% by mass.
[0091] The following describes an embodiment of the present invention.
[0092] [Example 1] <Preparation of the first particle (first step)> 430 g of silica alumina sol (Fine Cataloid USBB-120, manufactured by JGC Catalysts and Chemicals, average particle size 25 nm, solid content concentration 23% by mass) and 9.6 kg of pure water were mixed and heated to 98° C. A 1% by mass aqueous sodium hydroxide solution was added thereto to adjust the pH to 12.5.
[0093] To this mixture, 10.2 kg of sodium silicate aqueous solution (SiO2 concentration 3.0 mass%) and 10.2 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0 mass%) were added simultaneously. Next, 37.5 kg of sodium silicate aqueous solution (SiO2 concentration 3.0 mass%) and 12.5 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0 mass%) were added simultaneously. During this time, the temperature of the reaction liquid was maintained at 98°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid content concentration of 3 mass%.
[0094] To 50 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 10 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 131 g of a 10% by mass aqueous sodium hydroxide solution was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of these particles was 0.2% by mass.
[0095] <Supporting antibacterial metal component (second step)> Next, 500 g of an aqueous dispersion of the first particles diluted to 1.5% by mass with pure water was adjusted to 30° C., and 70.8 g of a 1.0% by mass aqueous silver nitrate solution was added over 30 minutes while stirring, followed by heat treatment for 3 hours at 95° C. After cooling to room temperature, the mixture was washed with an ultrafiltration membrane and concentrated to obtain an aqueous dispersion of silica-based particles with a solid content concentration of 1.5% by mass.
[0096] Next, 500g of the aqueous dispersion of the silica-based particles was ion-exchanged for 3 hours using 200g of a cation exchange resin (Diaion SK1B, manufactured by Mitsubishi Chemical Corporation), and then ion-exchanged for 3 hours using 100g of an anion exchange resin (Diaion SA20A, manufactured by Mitsubishi Chemical Corporation). After that, ion-exchanged for 3 hours at 80°C using 100g of a cation exchange resin (Diaion SK1B, manufactured by Mitsubishi Chemical Corporation) to produce 160g of an aqueous dispersion of the particles of the present invention. The solid content of this dispersion was 5% by mass, and the Na2O content of the particles was 50 ppm.
[0097] The particles were measured by the following methods. The characteristics and properties of the particles in each manufacturing process are shown in Table 1 (the same applies to the following Examples. Comparative Examples are shown in Table 2).
[0098] The physical properties of the particles were measured by image analysis.
[0099] Specifically, the particle dispersion was first diluted to 0.01% by mass, and then dried on a collodion film of a copper cell for an electron microscope. Then, this was photographed at a magnification of 1,000,000 times using a field emission transmission electron microscope (HF5000 manufactured by Hitachi High-Technologies Corporation). For 1,000 particles randomly selected from the obtained photographic projections (SEM images, TEM photographs), each item was measured by the following methods (1) to (4).
[0100] (1) Particle size The particle area was calculated from the SEM image processing, and the equivalent circle diameter was calculated from the area. The average of the equivalent circle diameters was taken as the particle size.
[0101] (2) Shell thickness From the TEM photographs, the thicknesses of the inside and outside of the shell were obtained for particles having a cavity inside the shell, and the average value was taken as the coating thickness.
[0102] (3) Porosity The particle diameter of the particles having a cavity inside the outer shell and the shell thickness obtained in (2) above were used to determine their respective volumes, and the volume of the inside of the particle relative to the total particle volume was calculated. The average of these volumes was taken as the porosity.
[0103] (4) The ratio of particles with one cavity to the total number of particles The number of cavities in the particles was counted from the TEM photographs, and the ratio of particles with one cavity to the total number of particles was calculated.
[0104] (5) Content of antibacterial metal elements, metal elements other than silicon that compose the outer shell, alkali metals, and alkaline earth metals The content of antibacterial metal elements (Ag, Cu, Zn, Pb, Sn, Bi, Cd, Cr, Hg, Ni, Co) in the particles, the content of metal elements other than silicon that make up the outer shell (Al, Zr, Ti, Zn, Sn, Sb), the content of alkali metals, and the content of alkaline earth metals were measured by dissolving the particles in hydrofluoric acid, heating to remove the hydrofluoric acid, and then adding pure water as necessary.The resulting solution was then measured using an ICP inductively coupled plasma optical emission spectrometer / mass spectrometer (ICP-8500, manufactured by Shimadzu Corporation).
[0105] (6) Silica content The particle dispersion was dried at 120°C for 12 hours, and the silica (SiO2) content was determined using an X-ray fluorescence analyzer (EA600VX, manufactured by Hitachi High-Tech Science Corporation).
[0106] (7) Density determined by He gas adsorption method (A1) and density determined by N2 gas adsorption method (B1) The particle dispersion liquid was dried in an evaporator and then dried at 105° C. The powder was placed in a cell and measured using a dry automatic density meter (Micromeritics Corporation, AccuPyc1340TC) with He gas or N2 gas at a gas introduction pressure of 134 kPa for 10 measurements.
[0107] (8) The density (A2) of the 400°C heat-treated sample determined by the He gas adsorption method, and the ratio (A2 / B2) of the density (A2) to the density (B2) determined by the N2 gas adsorption method The particle dispersion was dried in an evaporator, and then heat-treated (calcined) in air at 400°C for 1 hour. The powder was placed in a cell, and measurements were taken using a dry automatic density meter (Micromeritics AccuPyc1340TC) with He gas or N2 gas, 10 measurements at a gas introduction pressure of 134kPa, to determine the ratio (A2 / B2).
[0108] (9) Organic compounds having functional groups The presence or absence of functional groups contained in the particles and the types thereof were determined by the following method.
[0109] First, the particle dispersion liquid was dried in an evaporator and then dried at 105° C. The powder was subjected to a diffuse reflection method using a Fourier transform infrared spectrometer (FT-IR) (FT / IR-6100 manufactured by JASCO Corporation) in the wave number region of 700 cm. -1 ~4000cm -1 , detector: TGS, resolution: 4.0 cm -1 The measurement was performed with 50 accumulations, peaks were detected, and functional groups were identified by referring to the organic compound spectrum database SDBS (https: / / sdbs.db.aist.go.jp (National Institute of Advanced Industrial Science and Technology, 2021.01)).
[0110] However, no peaks due to functional groups were observed for these particles, because the particles were not surface-treated with an organosilicon compound such as 3-methacryloxypropyltrimethoxysilane as in other examples.
[0111] <Production of Coating Solution for Coating Formation> The solvent in 160 g of the aqueous dispersion of the particles was replaced with ethanol using an ultrafiltration membrane to obtain an ethanol dispersion of the particles with a solid content concentration of 5% by mass. The Na2O content of the particles was 50 ppm.
[0112] To 96 g of an ethanol dispersion of these particles, 2.30 g of dipentaerythritol hexaacrylate (DPE-6A manufactured by Kyoeisha Chemical Co., Ltd., solid content concentration 100% by mass), 0.58 g of 1,6-hexanediol diacrylate (A-HD-N manufactured by Shin-Nakamura Chemical Co., Ltd., solid content concentration 100% by mass), 0.19 g of reactive silicone oil for water repellent materials (X-22-174DX manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration 100% by mass), 0.43 g of silicone modified polyurethane acrylate (Shikou UT-4314 manufactured by Nippon Synthetic Chemical Industry Co., Ltd., solid content concentration 30% by mass), and a photopolymerization initiator (Omnirad manufactured by IGM Resins BV) were added as matrix forming components. 0.14 g of TPO (solid content concentration 100% by mass) and 50.2 g of isopropyl alcohol, 30.1 g of methyl isobutyl ketone, and 20.1 g of isopropyl glycol as organic solvents were mixed to produce a coating liquid for forming a coating film with a solid content concentration of 4% by mass.
[0113] <Production of coated substrate> A hard coat paint (ELCOM HP-1004, manufactured by JGC Catalysts and Chemicals Co., Ltd.) was applied to a TAC film (FT-PB80UL-M, manufactured by PANAC Co., Ltd., thickness 80 μm, refractive index 1.51) using a bar coater method (#18) and dried at 80 °C for 120 seconds. Then, 300 mJ / cm 2 The hard coat film was then cured by irradiation with ultraviolet light of 1000 ohms to prepare a hard coat film. The hard coat film had a thickness of 8 μm.
[0114] Next, the prepared coating solution was applied by a bar coater method (#4) and dried at 80°C for 120 seconds. Then, it was dried at 400 mJ / cm2 under a N2 atmosphere. 2 The coating was cured by exposure to ultraviolet light of 1000 ohms to produce a coated substrate.
[0115] The coated substrate was measured for the following items, and the results are shown in Table 3 (the same applies to the following Examples and Comparative Examples).
[0116] (10) Appearance The obtained coated substrate was visually inspected for the presence or absence of foreign matter defects. No foreign matter defects found: ◎ Slight foreign matter defects: ○ Many foreign body defects found: △ Foreign matter defects are present throughout: ×
[0117] (11) Film thickness and reflectance The film thickness and reflectance at a wavelength of 550 nm of the coated substrate were measured using an ellipsometer (EMS-1, manufactured by ULVAC Corporation).
[0118] (12) Haze, total light transmittance The haze and total light transmittance of the coated substrate were measured using a haze meter (manufactured by Suga Test Instruments Co., Ltd.).
[0119] (13) Antibacterial testing The antibacterial test was carried out in accordance with JIS Z 2801, and the antibacterial activity value was calculated according to the following formula (2).
[0120] Q=Ut-At...Equation (2) (where Q is the antibacterial activity value, Ut is the 1cm 2 At is the average logarithmic value of the number of viable bacteria per cm2 of the antibacterial treated test piece after 24 hours. 2 The mean logarithmic value of the number of viable bacteria per sample is shown.)
[0121] The test bacteria used were Staphylococcus aureus (NBRC 12732) and Escherichia coli (NBRC3972), and the nutrients used were 1 / 20 concentration of nutrient broth (meat extract 150 mg / L + peptone 250 mg / L).
[0122] For the measurement, 0.4 mL of the bacterial solution was dropped onto the coated substrate and untreated film cut into 5 cm squares, and then covered with a 4 cm square PE film. The test pieces were incubated at 35°C ± 1°C and a relative humidity of 90% or more for 24 hours, and the test bacteria on the test pieces were washed out and collected, then 2 The number of viable bacteria per unit area was determined.
[0123] (14) Measurement of scratch resistance #0000 steel wool, load 1000g / cm 2 After sliding, the surface of the coated substrate was visually observed and evaluated according to the following criteria. Evaluation criteria; No streaky scratches: ◎ Slight streak marks: ○ Numerous streak-like scratches are observed: △ The entire surface is scraped off: ×
[0124] (15) Adhesion The surface of the coated substrate was scratched with a knife in 11 parallel lines spaced 1 mm apart to create 100 squares. Cellophane tape was then adhered to the surface, and the adhesion was evaluated by classifying the number of squares that remained without the coating when the cellophane tape was peeled off into the following three levels. Number of remaining squares: 95 or more: ◎ Number of remaining squares: 90-94: Number of remaining squares: 85-89: △ Number of remaining squares: 84 or less: ×
[0125] [Example 2] In the same manner as in Example 1, 128 g of an ethanol dispersion of particles with a solid content concentration of 5% by mass was obtained. 0.32 g of 3-methacryloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) was added thereto, and heat treatment was performed at 30°C for 24 hours. Thereafter, the solvent was replaced with methyl isobutyl ketone (MIBK) using an evaporator, and an MIBK dispersion of particles with a solid content concentration of 5% by mass was produced. The Na2O content of these particles was 50 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the MIBK dispersion of particles was used, and each property was evaluated.
[0126] [Example 3] In the second step, a particle MIBK dispersion with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that 7.8 g of an aqueous silver nitrate solution was used. The Na2O content of these particles was 50 ppm. Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the particle MIBK dispersion was used, and each characteristic was evaluated.
[0127] [Example 4] In the second step, 920 g of silver nitrate aqueous solution was used, and the addition time was 90 minutes, but in the same manner as in Example 2, a particle MIBK dispersion with a solid content concentration of 5 mass% was produced. The Na2O content of these particles was 50 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the particle MIBK dispersion was used, and each characteristic was evaluated.
[0128] [Example 5] <Preparation of the first particle (first step)> 10 g of silica sol (CATALOID SI-550, manufactured by JGC C&C, average particle size 5 nm, SiO2 concentration 20.5% by mass) and 10.0 kg of pure water were mixed and heated to 50° C. A 1% by mass aqueous sodium hydroxide solution was added to adjust the pH to 10.5.
[0129] To this mixture, 7.9 kg of sodium silicate aqueous solution (SiO2 concentration 3.0 mass%) and 7.9 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0 mass%) were added simultaneously. Next, 51.8 kg of sodium silicate aqueous solution (SiO2 concentration 3.0 mass%) and 17.1 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0 mass%) were added simultaneously. During this time, the temperature of the reaction liquid was maintained at 50°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid content concentration of 3 mass%.
[0130] To 50 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 18 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Then, 236 g of a sodium hydroxide aqueous solution with a concentration of 10% by mass was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of these particles was 0.3% by mass.
[0131] In the second step, a MIBK dispersion of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that the first particles were diluted to 1.5 mass% with pure water. The Na2O content of these particles was 90 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the MIBK dispersion of the particles was used, and each characteristic was evaluated.
[0132] [Example 6] <Preparation of the first particle (first step)> 10 g of silica sol (CATALOID SI-50, manufactured by JGC C&C, average particle size 25 nm, SiO2 concentration 48% by mass) and 5.0 kg of pure water were mixed and heated to 98° C. A 1% by mass aqueous sodium hydroxide solution was added to adjust the pH to 12.5.
[0133] To this mixture, 65 kg of an aqueous sodium silicate solution (SiO2 concentration 1.5% by mass) and 65 kg of an aqueous sodium aluminate solution (Al2O3 concentration 0.5% by mass) were added simultaneously. Next, 37 kg of an aqueous sodium silicate solution (SiO2 concentration 1.5% by mass) and 12 kg of an aqueous sodium aluminate solution (Al2O3 concentration 0.5% by mass) were added simultaneously. During this time, the temperature of the reaction solution was maintained at 98°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid content concentration of 3% by mass.
[0134] To 50 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 5 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 66 g of a sodium hydroxide aqueous solution with a concentration of 10% by mass was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of these particles was 0.2% by mass.
[0135] In the second step, a MIBK dispersion liquid of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that the first particles were diluted to 1.5 mass% with pure water. The Na2O content of these particles was 30 ppm.
[0136] <Production of Coating Solution and Coated Substrate> 32g of the MIBK dispersion of particles was mixed with 4.61g of dipentaerythritol hexaacrylate, 1.15g of 1,6-hexanediol diacrylate, 0.38g of reactive silicone oil for water repellent, 0.85g of silicone modified polyurethane acrylate and 0.29g of photopolymerization initiator as matrix forming components, and 80.4g of isopropyl alcohol, 48.2g of methyl isobutyl ketone and 32.1g of isopropyl glycol as organic solvents to obtain a coating solution with a solid content concentration of 4% by mass. Next, a coated substrate was produced in the same manner as in Example 1 except that this coating solution was used, and each characteristic was evaluated.
[0137] [Example 7] <Preparation of the first particle (first step)> 313 g of silica alumina sol (Fine Cataloid USBB-120, manufactured by JGC Catalysts and Chemicals Co., Ltd.) and 29.7 kg of pure water were mixed and heated to 98° C. An aqueous solution of sodium hydroxide with a concentration of 1% by mass was added thereto to adjust the pH to 12.5.
[0138] To this mixture, 30.0 kg of sodium silicate aqueous solution (SiO2 concentration 3.0 mass%) and 30.0 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0 mass%) were added simultaneously. Next, 70.0 kg of sodium silicate aqueous solution (SiO2 concentration 1.5 mass%) and 23.3 kg of sodium aluminate aqueous solution (Al2O3 concentration 0.5 mass%) were added simultaneously. During this time, the temperature of the reaction liquid was maintained at 98°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid content concentration of 3 mass%.
[0139] To 50 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 9 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 118 g of a sodium hydroxide aqueous solution with a concentration of 10% by mass was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of these particles was 0.1% by mass.
[0140] In the second step, a MIBK dispersion of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that the first particles were diluted to 1.5 mass% with pure water. The Na2O content of these particles was 30 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the MIBK dispersion of particles was used, and each characteristic was evaluated.
[0141] [Example 8] <Preparation of the first particle (first step)> 63 g of silica sol (CATALOID SI-50, manufactured by JGC C&C Co., Ltd.) and 29.9 kg of pure water were mixed and heated to 98° C. A 1% by mass aqueous sodium hydroxide solution was added thereto to adjust the pH to 12.5.
[0142] To this mixture, 10.7 kg of sodium silicate aqueous solution (SiO2 concentration 3.0% by mass) and 10.7 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0% by mass) were added simultaneously. Next, 86 kg of sodium silicate aqueous solution (SiO2 concentration 3.0% by mass) and 28.6 kg of sodium aluminate aqueous solution (Al2O3 concentration 1.0% by mass) were added simultaneously. During this time, the temperature of the reaction liquid was maintained at 98°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid content concentration of 3% by mass.
[0143] To 40 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 13 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 170 g of a sodium hydroxide aqueous solution with a concentration of 10% by mass was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of these particles was 0.2% by mass.
[0144] In the second step, a MIBK dispersion liquid of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that the first particles were diluted to 1.5 mass% with pure water. The Na2O content of these particles was 0.018 mass%.
[0145] <Production of Coating Solution and Coated Substrate> 56g of the MIBK dispersion of particles was mixed with 3.74g of dipentaerythritol hexaacrylate, 0.94g of 1,6-hexanediol diacrylate, 0.31g of reactive silicone oil for water repellent, 0.69g of silicone modified polyurethane acrylate and 0.23g of photopolymerization initiator as matrix forming components, and 69.0g of isopropyl alcohol, 41.4g of methyl isobutyl ketone and 27.6g of isopropyl glycol as organic solvents to produce a coating solution with a solid content concentration of 4% by mass. Next, a coated substrate was produced in the same manner as in Example 1 except that this coating solution was used, and each characteristic was evaluated.
[0146] [Example 9] <Preparation of the first particle (first step)> 52 g of silica sol (CATALOID SI-50, manufactured by JGC C&C Co., Ltd.) and 4.9 kg of pure water were mixed and heated to 98° C. A 1% by mass aqueous sodium hydroxide solution was added thereto to adjust the pH to 12.5.
[0147] To this mixture, 77 kg of a sodium silicate aqueous solution (SiO2 concentration 1.0 mass%) and 86 kg of a sodium aluminate aqueous solution (Al2O3 concentration 0.3 mass%) were added simultaneously. Next, 92 kg of a sodium silicate aqueous solution (SiO2 concentration 1.0 mass%) and 34 kg of a sodium aluminate aqueous solution (Al2O3 concentration 0.3 mass%) were added simultaneously. During this time, the temperature of the reaction liquid was maintained at 98°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid concentration of 3 mass%.
[0148] To 50 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 9 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 118 g of a sodium hydroxide aqueous solution with a concentration of 10% by mass was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of these particles was 0.2% by mass.
[0149] In the second step, a MIBK dispersion liquid of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that the first particles were diluted to 1.5 mass% with pure water. The Na2O content of these particles was 40 ppm.
[0150] <Production of Coating Solution and Coated Substrate> 64g of the particle MIBK dispersion was mixed with 3.46g of dipentaerythritol hexaacrylate, 0.86g of 1,6-hexanediol diacrylate, 0.29g of reactive silicone oil for water repellent, 0.64g of silicone modified polyurethane acrylate and 0.22g of photopolymerization initiator as matrix forming components, and 65.3g of isopropyl alcohol, 39.2g of methyl isobutyl ketone and 26.1g of isopropyl glycol as organic solvents to produce a coating solution with a solid content concentration of 4% by mass. Next, a coated substrate was produced in the same manner as in Example 1 except that this coating solution was used, and each characteristic was evaluated.
[0151] [Example 10] In the second step, 500 g of the aqueous dispersion of silica-based particles was ion-exchanged with 100 g of cation exchange resin for 3 hours, and the subsequent ion exchange with anion exchange resin and cation exchange resin were not performed, so that an MIBK dispersion of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2. The Na2O content of these particles was 0.09 mass%. Next, a coating solution and a coated substrate were produced in the same manner as in Example 2, so that each property was evaluated, so that an MIBK dispersion of particles was used.
[0152] [Example 11] In the second step, an aqueous dispersion of particles was obtained in the same manner as in Example 1, except that 42.5 g of an aqueous silver nitrate solution was used. The Na2O content of the particles was 60 ppm. Next, an MIBK dispersion of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that 1.92 g of 3-methacryloxypropyltrimethoxysilane was used in the ethanol dispersion of particles with a solid content concentration of 5 mass% produced in the same manner as in Example 1. The Na2O content of the particles was 50 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the MIBK dispersion of particles was used, and each property was evaluated.
[0153] [Example 12] A 50 kg dispersion of silica-alumina particles prepared in the same manner as in Example 1 was adjusted to pH 1.0 by dropping concentrated hydrochloric acid with a concentration of 35.5% by mass, and dealumination was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane, and then concentrated hydrochloric acid with a concentration of 35.5% by mass was dropped again to adjust the pH to 0.3, and dealumination was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain a 10 kg dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 131 g of a 10% by mass aqueous sodium hydroxide solution was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O content of this particle was 0.2% by mass, and the Al2O3 content was 0.00% by mass.
[0154] In the second step, the first particles diluted to 1.5% by mass with pure water were used, and an MIBK dispersion of particles with a solid content concentration of 5% by mass was produced in the same manner as in Example 1, except that 14.2 g of an aqueous silver nitrate solution was used. The Na2O content of these particles was 30 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that an MIBK dispersion of particles was used, and each characteristic was evaluated.
[0155] [Example 13] In the second step, a MIBK dispersion of particles with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that 132.8 g of a copper nitrate aqueous solution was used instead of the silver nitrate aqueous solution. The Na2O content of these particles was 50 ppm. Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the MIBK dispersion of particles was used, and each characteristic was evaluated.
[0156] [Example 14] In the second step, a particle MIBK dispersion with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that 130.3 g of a zinc nitrate aqueous solution was used instead of the silver nitrate aqueous solution. The Na2O content of these particles was 50 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the particle MIBK dispersion was used, and each characteristic was evaluated.
[0157] [Example 15] <Production of Coating Solution and Coated Substrate> 64 g of the MIBK dispersion of the particles produced in Example 9 was mixed with 3.11 g of dipentaerythritol hexaacrylate, 0.77 g of 1,6-hexanediol diacrylate, 2.16 g of fluorine-based resin (Optool DAC-HP manufactured by Daikin Industries, Ltd., solid content concentration 20% by mass), 0.48 g of fluorine-based additive (Megafac F477 manufactured by DIC Corporation, active ingredient 100%) and 0.22 g of photopolymerization initiator as matrix forming components, and 65.3 g of isopropyl alcohol, 39.2 g of methyl isobutyl ketone and 24.8 g of isopropyl glycol as organic solvents to produce a coating solution with a solid content concentration of 4% by mass. Next, a coated substrate was produced in the same manner as in Example 1 except that this coating solution was used, and each property was evaluated.
[0158] [Example 16] <Preparation of Coating Solution for Forming High Refractive Index Layer> 26 g of titania-based sol (ELCOM V-9108 manufactured by JGC Catalysts and Chemicals, particle size 15 nm, solid content concentration 30.5% by mass) was mixed with 1.44 g of dipentaerythritol hexaacrylate, 0.36 g of 1,6-hexanediol diacrylate, and 0.1 g of photopolymerization initiator as matrix forming components, and 172 g of propylene glycol monomethyl ether as an organic solvent to obtain a coating liquid for forming a high refractive index layer with a solid content concentration of 5% by mass.
[0159] <Production of coated substrate> The above-mentioned coating solution for forming a high refractive index layer was applied to a TAC film having a hard coat film prepared in the same manner as in Example 1 by a bar coater method (#8), and dried at 80°C for 120 seconds. 2 The high refractive index layer was formed by irradiating the resin with ultraviolet light of 1000 nm and curing the resin. The high refractive index layer had a thickness of 220 nm.
[0160] Next, the coating solution prepared in Example 9 was applied by a bar coater method (#4) and dried at 80°C for 120 seconds. Then, it was dried at 400 mJ / cm2 under a N2 atmosphere. 2The coating was cured by exposure to ultraviolet light of 1000 ohms to produce a substrate with a coating, and each of the properties was evaluated.
[0161] [Example 17] <Preparation of coating solution for forming anti-glare layer> 10 g of silica powder (Silica Microbead P-500, manufactured by JGC Catalysts and Chemicals Co., Ltd.) was mixed with 30.2 g of dipentaerythritol hexaacrylate, 7.6 g of 1,6-hexanediol diacrylate, and 1.9 g of a photopolymerization initiator as matrix forming components, and 78.2 g of propylene glycol monomethyl ether as an organic solvent to obtain a coating liquid for forming an anti-glare layer with a solid content concentration of 35 mass %.
[0162] <Production of coated substrate (17)> The above-mentioned anti-glare layer-forming coating solution was applied to a TAC film having a hard coat film prepared in the same manner as in Example 1 by a bar coater method (#9), and dried at 80° C. for 120 seconds. Then, 800 mJ / cm 2 The coating was cured by exposure to ultraviolet light of 1000 ohms to prepare an anti-glare layer.
[0163] Next, the coating solution prepared in Example 9 was applied by a bar coater method (#4) and dried at 80°C for 120 seconds. Then, it was dried at 400 mJ / cm2 under a N2 atmosphere. 2 The coating was cured by exposure to ultraviolet light of 1000 ohms to produce a substrate with a coating, and each of the properties was evaluated.
[0164] [Comparative Example 1] In the second step, a particle MIBK dispersion with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that no silver nitrate aqueous solution was used, and 0.34 g of 3-methacryloxypropyltrimethoxysilane was used in 128 g of the particle ethanol dispersion. The Na2O content of the particles was 50 ppm. Next, a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the particle MIBK dispersion was used, and each characteristic was evaluated.
[0165] [Comparative Example 2] Silica sol (JGC Catalysts and Chemicals Co., Ltd., Cataloid SI-45P, particle size 60 nm, solid content concentration 40.5% by mass) was diluted with pure water to obtain 10 kg of silica sol with a solid content concentration of 5% by mass. Next, 131 g of a 10% by mass aqueous sodium hydroxide solution was added and heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of first silica-based particles. The Na2O concentration of these silica-based particles was 0.2% by mass. The silica-based particles were so-called "solid particles" that did not have any internal cavities.
[0166] In the second step, a silica-based particle MIBK dispersion with a solid content concentration of 5 mass% was produced in the same manner as in Example 2, except that the first silica-based particle diluted to 1.5 mass% with pure water was used. The Na2O content of this particle was 80 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the silica-based particle MIBK dispersion was used, and each characteristic was evaluated.
[0167] [Comparative Example 3] <Production of silver nanoparticles> While bubbling nitrogen gas into 729 g of 30% by mass aqueous sodium citrate solution, 65 g of 25% by mass iron sulfate (II) was added. After stirring for 30 minutes, 24 g of 10% by mass silver nitrate was added all at once and stirred for 6 hours. The mixture was centrifuged at 5000 rpm for 10 minutes, the precipitate was collected, and suspended in 270 g of pure water by ultrasonic waves to obtain an aqueous dispersion of silver nanoparticles. Next, the solvent of 200 g of the aqueous dispersion of silver nanoparticles was replaced with IPA using an ultrafiltration membrane to produce an IPA dispersion of silver nanoparticles with a solid content concentration of 5.0% by mass. The particle diameter of the silver nanoparticles was 10 nm, and the Na2O concentration was 0 ppm. The particle properties shown in Table 2 are the properties when the particles produced in Comparative Example 1 and silver nanoparticles were mixed at a mass ratio of 95.4:4.6. However, the thickness and porosity of the outer shell were measured only for particles having a cavity inside the outer shell. The mixing ratio of the particles produced in Comparative Example 1 and the silver nanoparticles was adjusted so that the apparent porosity and antibacterial metal amount of the mixture were equivalent to those of the particles in Example 2.
[0168] <Production of Coating Solution and Coated Substrate> A coating solution and a coated substrate were produced in the same manner as in Example 1, except that a solution was used in which 91.6 g of the MIBK dispersion of the particles produced in Comparative Example 1, which did not contain an antibacterial metal component, and 4.4 g of the IPA dispersion of silver nanoparticles were mixed, and the respective characteristics were evaluated.
[0169] [Comparative Example 4] In the second step, 2120 g of silver nitrate aqueous solution was used, and the addition time was 90 minutes, but the same procedure as in Example 2 was used to produce a particle MIBK dispersion with a solid content concentration of 5 mass%. The Na2O content of these particles was 50 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the particle MIBK dispersion was used, and each characteristic was evaluated.
[0170] [Comparative Example 5] <Preparation of the first particle (first step)> 188 g of silica alumina sol (Fine Cataloid USBB-120, manufactured by JGC Catalysts and Chemicals Co., Ltd.) and 89.8 kg of pure water were mixed and heated to 98° C. A 1% by mass aqueous sodium hydroxide solution was added thereto to adjust the pH to 12.5.
[0171] To this mixture, 23.0 kg of a sodium silicate aqueous solution (SiO2 concentration 3.0% by mass) and 23.0 kg of a sodium aluminate aqueous solution (Al2O3 concentration 1.0% by mass) were added simultaneously. Next, 15.0 kg of a sodium silicate aqueous solution (SiO2 concentration 3.0% by mass) and 5.0 kg of a sodium aluminate aqueous solution (Al2O3 concentration 1.0% by mass) were added simultaneously. During this time, the temperature of the reaction solution was maintained at 98°C. Next, this was washed with an ultrafiltration membrane to obtain a dispersion of silica alumina particles with a solid content concentration of 3% by mass.
[0172] To 50 kg of this dispersion of silica-alumina particles, concentrated hydrochloric acid with a concentration of 35.5% by mass was added dropwise to adjust the pH to 1.0, and a dealumination process was performed. The dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain 9 kg of a dispersion of silica-based particles with a solid content concentration of 5% by mass. Next, 118 g of a sodium hydroxide aqueous solution with a concentration of 10% by mass was added. This was heat-treated in an autoclave at 195°C for 24 hours to obtain an aqueous dispersion of the first particles. The Na2O concentration of these particles was 0.1% by mass.
[0173] In the second step, a particle MIBK dispersion with a solid content concentration of 5.0 mass% was produced in the same manner as in Example 2, except that the first particles diluted to 1.5 mass% with pure water were used. The Na2O content of these particles was 40 ppm. Next, a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that the particle MIBK dispersion was used, and each characteristic was evaluated.
[0174] [Table 1]
[0175] [Table 2]
[0176] [Table 3]
Claims
1. The particles contain an antibacterial metal component in an amount of 0.5 to 40 mass% on an oxide basis, and have an outer shell containing silicon and a cavity inside the shell, the ratio of the cavities in the particle (porosity) is 10 to 90%, and the ratio of the number of particles each having one cavity to the number of all particles is 80% or more; The density (A1) of the particles dried at 105° C. by a He gas adsorption method is 1.95 to 3.50 g / ml, and the density (B1) of the particles dried at 105° C. by a N 2 gas adsorption method is 0.50 to 2.60 g / ml; The particles are characterized in that the density (A2) of the particles heat-treated at 400°C as measured by a He gas adsorption method is 2.17 g / ml or more, and the ratio (A2 / B2) of the density (A2) of the particles heat-treated at 400°C as measured by a N2 gas adsorption method is 1.10 to 4.
50.
2. 2. The particle according to claim 1, wherein the antibacterial metal component comprises at least one element selected from silver, copper, zinc, lead, tin, bismuth, cadmium, chromium, mercury, nickel, and cobalt.
3. The density (A1) of the particles dried at 105° C. by a He gas adsorption method is 2.10 to 2.30 g / ml, 2 2. The particle according to claim 1, characterized in that the density (B1) measured by a gas adsorption method is 0.80 to 2.10 g / ml.
4. The density (A2) of the particles heat-treated at 400° C. as determined by a He gas adsorption method is 2.17 g / ml or more, and the N 2 2. The particle according to claim 1, wherein the ratio (A2 / B2) to the density (B2) determined by a gas adsorption method is 1.30 to 4.
50.
5. 2. The particle according to claim 1, wherein the average particle size of the particle is 20 to 180 nm, and the average thickness of the shell is 5 to 30 nm.
6. 2. The particle according to claim 1, wherein the alkali metal content of the particle is less than 1.00% by weight on an oxide basis.
7. The particle of claim 1 , wherein the particle comprises an organic compound having a functional group.
8. A substrate with a transparent coating, comprising the particles according to claim 1 and a matrix, formed on the substrate.
9. 9. The substrate with a transparent coating according to claim 8, wherein at least one layer selected from a hard coat layer, a high refractive index layer, an anti-glare layer, and a conductive layer is disposed between the transparent coating and the substrate.
Citation Information
Patent Citations
One-step synthesized SiO2 nanocapsule inlaid with Ag nanoparticles and preparation method of SiO2 nanocapsule
CN107456930A
Silicon dioxide coated silver nanoparticle with multilevel hollow structure as well as synthesis method and application thereof
CN107999743A
Multiple oxide sol, its production and base material
JP1995133105A
Antimicrobial agent consisting of complex particle or hollow particle
JP1995196424A
Antireflection film
JP1999052105A